2021
DOI: 10.3346/jkms.2021.36.e2
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a Predictor of Prognosis in Early Stage Ovarian Cancer

Abstract: Background: To identify sarcopenia as a predictive prognostic factor of ovarian cancer in terms of survival outcome in patients with early-stage ovarian cancer. Methods: Data of Konkuk University Medical Center from March 2002 to December 2017 were reviewed retrospectively. Patients who underwent surgery due to early-stage (International Federation of Gynecology and Obstetrics stage I/II) ovarian cancer and had computed tomography (CT) images taken at the initial diagnosis were included. The initial CT scan im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…The third lumbar spine SMI is widely used for nutritional assessment and in the assessment of tumor prognosis. However, there is no uniform standard cut-off value (37). Staley, using SMI 41 as the cutoff value, evaluated 201 patients with epithelial ovarian cancer and found that sarcopenia was not associated with poor survival outcomes or chemotherapy toxicity.…”
Section: Skeletal Muscle Indexmentioning
confidence: 99%
“…The third lumbar spine SMI is widely used for nutritional assessment and in the assessment of tumor prognosis. However, there is no uniform standard cut-off value (37). Staley, using SMI 41 as the cutoff value, evaluated 201 patients with epithelial ovarian cancer and found that sarcopenia was not associated with poor survival outcomes or chemotherapy toxicity.…”
Section: Skeletal Muscle Indexmentioning
confidence: 99%
“…Sarcopenia occurs in approximately 50% of advanced cancer patients, being related to malnutrition, inflammation and tumor treatments [ 6 ]. In these patients, it has been demonstrated to be associated with worse outcomes in terms of overall survival (OS) and progression free survival (PFS), and it can be considered as a negative prognostic factor for different types of cancer, regardless of stage or treatment approach [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A positive trend was also shown for OS, but it was not statistically significant ( n = 5, adjusted HR: 1.27, 95% CI: 0.98; 1.64, p = 0.070, Table 6 ). The study of Chae et al [ 66 ] appeared to be an outlier and was therefore omitted from the analysis, resulting in a reduction in the estimated HR and heterogeneity ( Table 6 , Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“… a Study of Chae et al, 2021 was an outlier [ 66 ], b study of Kumar et al, 2016 was an outlier [ 19 ], c study of Inci et al, 2021 was an outlier [ 77 ]. Abbreviations: CI, confidence interval; HR, hazard ratio; I 2 , heterogeneity between studies; n, number of studies included in analysis; OR, odds ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation